Breton in "Modianoland": Occupied, Convalescent and Surreal City - Ramallo, Francisco (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2018)
The occupied town of Patrick Modiano has not been able to erase the Bretonian surreal city. It is associated with sensations such as disorientation and claustrophobia, and appeals to the imagination of the reader to solve the incidents that happen in it. Its design is the result of the selection of captivating spaces where, after being obscured by the war, happen improbable coincidences, the atmosphere is hazy, they seem dreamed because they are far, wounded, lonely, unheimlich.